2007
DOI: 10.21273/jashs.132.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Oxidase as a Cause of Variation in Oxygen Uptake Rates Among Vegetables

Abstract: ADDITIONAL INDEX WORDS. enzymatic activity, image analysis, staining, Brassica oleracea, Spinacia oleracea, Allium cepa ABSTRACT. The effect of cytochrome c oxidase, the terminal oxidase in the respiratory chain, on O 2 uptake by vegetables was investigated. Broccoli florets (Brassica oleracea L. var. italica Plenck), spinach leaves (Spinacia oleracea L.), and onion bulbs (Allium cepa L.), which were expected to show rapid, moderate, and slow O 2 uptake rates, respectively, were used in the current study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Values measured during storage at 1 • C in the present study and those reported by Makhlouf et al [8] were in the range of 0.59-0.80 mmol kg −1 h −1 and 0.26-0.63 mmol kg −1 h −1 , respectively. These are much lower than the values reported elsewhere: 2.5-11 mmol kg −1 h −1 at 25 • C by Wang et al [13]; 7.56 mmol kg −1 h −1 at 20 • C by Makino et al [19]; and 9.99 mmol kg −1 h −1 at 20 • C by Robinson et al [4]. The low values exhibited in the present study were likely caused by the low storage temperature, which also made it difficult to detect significant influences arising from the different atmospheres.…”
Section: Changes In O 2 Uptake Ratecontrasting
confidence: 60%
“…Values measured during storage at 1 • C in the present study and those reported by Makhlouf et al [8] were in the range of 0.59-0.80 mmol kg −1 h −1 and 0.26-0.63 mmol kg −1 h −1 , respectively. These are much lower than the values reported elsewhere: 2.5-11 mmol kg −1 h −1 at 25 • C by Wang et al [13]; 7.56 mmol kg −1 h −1 at 20 • C by Makino et al [19]; and 9.99 mmol kg −1 h −1 at 20 • C by Robinson et al [4]. The low values exhibited in the present study were likely caused by the low storage temperature, which also made it difficult to detect significant influences arising from the different atmospheres.…”
Section: Changes In O 2 Uptake Ratecontrasting
confidence: 60%
“…Two of the most important biogeochemical reactions on the planet, carbon fixation and respiration, are commonly quantified during oceanographic surveys without understanding the contribution of individual phylogenetic groups. The expression of cytochrome c oxidase 1 and ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) have been examined in both natural systems and organisms and shown to correlate with oxygen consumption or production rates ( Corredor et al , 2004 ; John et al , 2007 ; Makino et al , 2007 ; Singtripop et al , 2007 ). Thus we examined the transcription of polypeptide 1 of cytochrome c oxidase ( COX1 , encoded by mitochondrial genomes) and the large subunit of Rubisco ( rbcL , encoded by plastid genomes) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cytochrome c oxidase (COX) a respiratory protein complex in the mitochondrial respiratory chain also exhibits spectral characteristics (Appaix et al, ; Mason, Nicholls, & Cooper, ). Connections between O 2 consumption, COX, and spectral absorbance in vegetables have been shown (Makino, Ichimura, Kawagoe, & Oshita, ; Makino, Ichimura, Oshita, Kawagoe, & Yamanaka, ), but Umbach, Lacey, and Richter () argued against a direct functional link between alternative oxidase (AOX, another respiratory protein) and floral reflectance, which probably also applies to leaf O 2 consumption, AOX, and reflectance. Another possibility is that the recent discovery of an association between mitochondrial functions and cell wall properties in plants (Hu et al, ) may indirectly link surface reflectance with respiratory processes.…”
Section: Discussionmentioning
confidence: 99%